Prevalence, intensity, and dominance of ectoparasites in gourami (Osphronemus goramy) reared in floating net cage in Cirata Reservoir, West Java, Indonesia - Ingga Lies Dastin; Rudy Agung Nugroho; Nova Hariani; Retno Aryani; Hetty Manurung; Rudianto Rudianto (Aceh Journal of Animal Science, 2021)
The aimed of the study was to determine the prevalence, intensity and dominance of ectoparasites that infected gourami (Osphronemus goramy) which cultivated in floating net cages in Cirata reservoir, West Java. Present results showed that there were 22 gouramis infected with ectoparasites from 30 observed fish. The ectoparasites (Prevalence, Intensity and Dominance) found were Trichodina sp. (13.33%, 8.15 32.62%), Ichthyobodo sp. (3.33%, 1.00, 0.31%) Microsporadia (6.67%, 1.00, 0.31%), Carchesium granulatum (6.67%, 34.00, 20.92%), Cichligogyrus sp. (3.33%, 7.00, 2.15%), Dacthylogyrus sp. (20.00%, 2.00, 3.69%), Centrocestus sp. (6.67%, 3.00, 1.85%), Argulus sp. (56.67%, 6.94, 36.31%), Lerneae sp. (3.33%, 3.00, 0,92%), Gnatia sp. (3.33%, 1.00, 0.31%) and Hatschekia sp (3.33%, 1.00, 0.31%). The Argulus sp. had the highest prevalence with a percentage of 73.33% and becames the most dominant species with a percentage value of 36,31%. Meanwhile, Carchesium granulatum was an ectoparasite species that demonstrated the highest intensity of 34. Based on the diversity of ectoparasites, it was found as positive case that gourami cultivated in the Cirata reservoir have been infected with ectoparasites, especially from the species Argulus sp.